Report on the Determination of Fair Ex-Works Price and Fair Selling Price of Acetate Yarn produced by Sirsilk Limited - Government of India Tariff Commission (Government of India Tariff Commission, 1957)
The Tariff Commission report on Sirsilk Limited assesses the fair ex-works price and fair selling price of acetate yarn, addressing the company’s financial distress caused by high production costs and underpricing. Key findings highlight significant input costs, outstanding liabilities to the Andhra Pradesh Government, and the need for price adjustments to ensure sustainability. Recommended fair selling prices for bright and dull yarn range from Rs. 4.64 to Rs. 5.16 and Rs. 4.67 to Rs. 5.10 per lb., respectively. The report suggests government interventions, including excise duty removal on alcohol and favorable power rates, alongside capital restructuring measures such as converting loans into share capital and deferring interest payments. Strategic allocation of future profits and optimization of production capacity are emphasized to improve financial stability. Overall, the report outlines comprehensive steps to stabilize Sirsilk Limited and promote growth in the acetyl rayon sector.
Government of India Tariff Commission
Keywords: Sirsilk Limited; Acetate Yarn; Tariff Commission; Ex-Works Price; Fair Selling Price; Production Costs; Financial Restructuring; Government Support; Capital Restructuring; Production Optimization